Cartografia Geológica à escala 1:10.000 da região SW da Folha Geológica 9C - Porto - M. Oliveira (2010)
The aim of this work was to conduct a geological survey and integrate the collected field data into a graphical environment for further processing and development of a geological map of an area belonging to the Vila Nova de Gaia municipality. The study included, therefore, the geological mapping, at a scale of 1:10,000 of the SW area of the 9C Geological Sheet, covering a total of about 18 km2. In the studied area were distinguished sintectonic two-mica granites (Afurada granite and Porto granite), posttectonic biotite granites (Madalena granite and Lavadores granite), metamorphic rocks (Unit of Lourosa) and large areas of sedimentary alluvial rocks